Bauran Pemasaran dan Sharia Compliance Terhadap Loyalitas Pelanggan - Syarifuddin, Ahmad Dzul Ilmi; Mahesa, Akramunnas (LAA MAISYIR : Jurnal Ekonomi Islam, 2020)
This study adds to the influence of marketing mix and sharia compliance on customer loyalty of Avansa cars at PT. Haji Kalla Alauddin Branch who purchases through Islamic financing. 100 samples were selected using purposive technique. Data were analyzed using multiple regression. the results of the study concluded that the marketing mix: product, price, promotion, and location and sharia compliance partially influenced the customer loyalty of Avansa cars at PT. Haji Kalla Alauddin Branch who purchases through Islamic financing. The marketing mix and Sharia Compliance partially influence the customer loyalty of Avansa cars at PT. Haji Kalla Alauddin Branch who purchases cars through Islamic financing.